Increasing the Efficiency of Storage Plastic Pellet on Racking System: A Case Study - Jadkrud, Porameth; Muangpan, Thanyaphat (College of Asian Scholar Journal, 2024)
This research examines the storage format of plastic pellet products on the shelving of a Shuttle Rack Automated Storage (SRAS) system in the case of a full-service logistics company. The objective is to analyze the storage efficiency of the case study company and propose ways to increase space utilization efficiency. The product data of sub-warehouse No. 2 was collected from the Warehouse Management System (WMS) in January 2024 to study space utilization efficiency in the current storage system, which categorizes products by type (Commodity system)—subsequently, applied a Combination System for storing plastic pellets on SRAS shelves. The research findings indicate that the Combination System achieves a space utilization efficiency rate of 89.54%, which is 4.32% higher than the current storage system and exceeds the case study company’s target by 3.54%. Six new empty rows have been added to store new Lot No. For products totaling 378 pallets or 567 tons, the case study company can reduce the need to transfer products to rental warehouses, resulting in a cost reduction of 1,578,528 baht per year.